(untitled) (Filološke pripombe, 2019)
The result of the research „Dramatic geometry“ in selected dramas shows different approaches to dramaturgy in the same literary period. Ivo Vojnović practices a closed type of dramaturgy while Anton Pavlovich Cechov different models of the „situation in the triangle“. Vojnović’s character characterization is primarily psychological while Cechov’s is based on the dynamic of the „situations in triangle“ which are the instigators of the dramatic action and process of character formation with other dramatic elements.